2011
DOI: 10.1271/bbb.110452
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and Caffeine Improve Insulin Sensitivity and Glucose Tolerance in C57BL/6J Mice Fed a High-Fat Diet

Abstract: We have previously demonstrated that coffee and caffeine ameliorated hyperglycemia in spontaneously diabetic KK-A(y) mice. This present study evaluates the antidiabetic effects of coffee and caffeine on high-fat-diet-induced impaired glucose tolerance in C57BL/6J mice. C57BL/6J mice fed a high-fat diet were given regular drinking water (control group), or a 2.5-fold-diluted coffee or caffeine solution (200 mg/L) for 17 weeks. The ingestion of coffee or caffeine improved glucose tolerance, insulin sensitivity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
35
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 41 publications
4
35
0
1
Order By: Relevance
“…Control: n512 (saline: n55; insulin: n57); Coffee: n512 (saline: n55; insulin: n57). enhanced insulin sensitivity in both diabetic KK-A y mice and C57BL/6J mice fed a high-fat diet (4,5), both of which develop insulin resistance in peripheral tissues. However, the mechanisms underlying the improvement of insulin sensitivity by coffee ingestion remained to be clarified in these diabetic models.…”
Section: Discussionmentioning
confidence: 99%
“…Control: n512 (saline: n55; insulin: n57); Coffee: n512 (saline: n55; insulin: n57). enhanced insulin sensitivity in both diabetic KK-A y mice and C57BL/6J mice fed a high-fat diet (4,5), both of which develop insulin resistance in peripheral tissues. However, the mechanisms underlying the improvement of insulin sensitivity by coffee ingestion remained to be clarified in these diabetic models.…”
Section: Discussionmentioning
confidence: 99%
“…14 Third, caffeine can activate Akt phosphorylation. 11,12,14 Fourth, caffeine intake did not affect circulating insulin secretion significantly. 40 Finally, caffeine does not alter the phosphorylation of the insulin receptor, IRS1-associated PI3K, or Akt S473 .…”
mentioning
confidence: 82%
“…Epidemiological studies have shown that long-term caffeine consumption diminishes diabetic symptoms by enhancing insulin sensitivity through more efficient insulin signaling. 11,12 However, although some studies have shown that acute caffeine consumption elevates BP, other studies have shown that habitual coffee intake is less likely to increase BP. 13,14 In fact, current studies have suggested a protective role of coffee intake against hypertension.…”
Section: S307mentioning
confidence: 99%
“…In KK-A y mice, which spontaneously develop type 2 diabetes, coffee ingestion suppressed hyperglycemia, hyperinsulinemia, hyperlipidemia, and hepatic steatosis (3). In C57BL/6J mice fed a high-fat diet, coffee ingestion also improved insulin sensitivity (4). Furthermore, we found that coffee increased the activation of Akt in insulin signaling in the liver and skeletal muscle (5).…”
mentioning
confidence: 62%
“…Previously we reported that coffee had an anti-diabetic effect in both spontaneous and diet-induced type 2 diabetes in animal models (3,4). In KK-A y mice, which spontaneously develop type 2 diabetes, coffee ingestion suppressed hyperglycemia, hyperinsulinemia, hyperlipidemia, and hepatic steatosis (3).…”
mentioning
confidence: 96%